Phytochemistry and biological properties of Drimys winteri JR et G. Forster var chilensis (DC) A - Munoz, Orlando; Tapia-Merino, Jorge; San Martin Barrientos, Aurelio Del Carmen; San-Martin, Aurelio (My University, 2021)
Drimys winteri JR et G. Forster var chilensis (DC) A. is a tree native to central and southern Chile. Also it found in part of Argentina. It is abundant in wet swampy localities from sea level to an altitude of 1700 m. This tree is sacred for the Mapuche culture; it is used in folk medicine in such as inflammatory and painful processes. Phytochemical studies have demonstrated that this plant contains mainly sesquiterpenes of the drimane type, flavonoids, essential oils, phytosterols and some lignans. These drimanes have attracted interest because of their antifeedant, plant growth regulation, cytotoxic, antimicrobial and insecticidal properties. The objective of this review is to establish clearly the phytochemistry and biological activity of Drimys winteri JR et G. Forster var chilensis (DC) A. Articles based on other varieties are not considered.
Keywords: drimys winteri; sesquiterpenes; essential oils; lignans; flavonoids; biological properties